La Competitividad en una Empresa Forestal Comunitaria (2020)
Forest utilization plays a fundamental role for the supply of raw material to the forest industry and the socio-economic development of forest communities, given its natural potential in providing goods and services. There are several studies of forest management, but few on competitiveness of productive chains. The present investigation was carried out in the forest community of Capulalpam de Méndez, Ixtlán, Oaxaca, Mexico and is considered a non-experimental design because the phenomenon was observed as it occurs in its natural context, to later analyze it without manipulating variables The results obtained show that the indicators: Productivity, product quality, profitability and market share, with values ​​of 0.75, 0.75, 0.70 and 0.62 respectively, are the most important indicators that determine the achievement of the company's competitiveness.